APPLICATIONS FOR E-COMMERCE SALES BY HANDPHONE ONLINE ON USING JOOMLA SUKMA CELLULAR AND XAMPP - Rianne Gloria Siregar; Diyah Ruri Irawati, SKom., MMSI (Jurnal Sistem Informasi, 2009)
E-commerce is the process of buying and selling services or products between bothparties through the Internet. E-commerce is also a kind of mechanism electronicbusiness with a focus on individual-based business transactions with use the Internetas a medium of exchange of goods or services, both among agencies or individualswith institutions.In this globalization era, the sale and purchase of many conduct transactions on theInternet. There are putting stuff in the blog, as well as sites like Friendster andFacebook had become an arena for selling.In designing e-commerce for the online mobile phone sales will discuss how to createan online store that is open 24 hours will facilitate sales and purchases without havingto come directly into store.